Operational administrative problems in a mediumsize enterprise - De la Garza Villarreal, Mario Alberto (UANL. Facultad de Contaduría Publica y Administración, 2014)
The first operational administrative problem presented was that the enterprise was working in the same way in many years; the workers used the same tool and the same procedures that were not effective, the method they used as solution was the concepts of ‘’5’s’’ to achieve having order and cleaning for the storage. The results were positive because they begin to have benefits such as optimize the process of shipping of merchandise to customers. Another important problem that had the enterprise was that they didn’t have well-defined processes, it affected when two areas entered when sales were made more concrete, the method they used as solution was de ‘’Ishikawa diagram’’ through the analysis cause-effect. It was missing improve the process for document the information in their system, TI support them and as result they achieve streamline prices and conditions of payments agreed with the customer.